Characterizing the Marine Energy Test Area (META) in Wales, UK - Iain Fairley (Renewable Energy, 2023)
With lack of convergence on any single wave or tidal technology, test centres have a unique role in the marine renewable energy industry. Test centres facilitate real testing at sea for devices and components at various TRLs (Technology Readiness Level), reducing the time, cost, and risks faced by marine energy developers. META (Marine Energy Test Area) is a £2.7M project managed by Marine Energy Wales (MEW), consisting of eight test areas in the Milford Haven Waterway and surrounding waters (Pembrokeshire, Wales). Although various datasets have been collected from the META test areas over the last decade, and some aspects of these data have been published in various reports, the data has not been gathered together, systematically analysed and critically assessed – the aim of this study. Here, we describe and interpret the various META datasets, including multibeam, ADCP (acoustic Doppler current profiler), and wave buoy data. We report the key parameters of relevance to testing at META, including bathymetry, the nature and magnitude of the tidal currents, turbulence, and wave climates. We make recommendations on future priorities for data collection at META, and discuss the future of the test areas, including expansion into floating wind and other evolving marine energy technologies.